Perspektif Studi Kewarganegaraan dalam Menganalisis Keragaman Kultur - Catur Ambyah Budiono; Muhammad Turhan Yani; Sarmini (EduInovasi: Journal of Basic Educational Studies, 2024)
Citizenship education is taught to instill a sense of nationalism and foster the nation's moral values ​​in order to achieve the glory and glory of a nation, as well as foster a sense of love for one's country and pride in being a citizen of a nation. If citizenship education is not implemented, the noble values ​​of the nation that have been formed long ago will simply disappear and will ultimately create disorganized social, national and state life and lead to destruction. The method used in this research is literature study using educational articles and also theses. By using a descriptive research approach, this research is intended to explain in more detail the topic raised as the main topic and also a specific explanation of the data sources that have been obtained. The results of this research show that from a citizenship studies perspective, cultural diversity in Indonesia is very complex and has characteristics in accordance with a citizenship studies perspective. Pancasila is one of the perspectives of Pancasila studies, where Pancasila in this context is a lens for viewing cultural diversity itself as in its implementation. every principle in Pancasila.